Community Service Material "Education Of Village Working Groups In The Environmental Sanitation Program In Cimenyan Village, Cimenyan District, Bandung District" - R. Taqwaty.Firdausijah; Lia Muliawaty (Jurnal Info Sains : Informatika dan Sains, 2023)
Villages in West Java have a lot of potential that can be developed to improve the welfare of their communities, but village development often experiences obstacles, one of which is in Cimenyan Village, Cimenyan District, Bandung Regency. This research uses qualitative methods with the aim of seeing how the sanitation program is carried out by village working groups in the Cimenyan area, Bandung Regency. The results of this research explain that environmental sanitation is an effort that can be made to achieve a clean and healthy environment through controlling physical factors, especially controlling things that appear to damage the environment. Implementing development is one of the agendas that the Amin Jaya Village government continues to carry out every year. These development programs are designed to meet the needs of the community and village government institutions. Development implementation begins with planning and design through a village deliberation forum involving the village government, BPD and community institutions.